Kepemimpinan Menteri Wanita Dalam 10 Tahun Pemerintahan Jokowi - Yeka Ramadhani; Evy Ratna Kartika Waty; Mega Nurrizalia; Miranti Miranti; Maisaro Maisaro; Aunil Mulki (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article discusses leadership of female ministers in Indonesia during the Jokowi administration, with a focus on roles and achievements them in various sectors. This report highlighting the importance of women in Indonesian politics, especially in context democratic transition in this country. This article also explore its challenges faced by women in positions leadership and strategies used by women to overcome obstacles the. This article uses qualitative research approach analyze the experiences and achievements of para female ministers in Indonesia at that time Jokowi government. This study utilize existing literature and data from various sources, including articles news and official records, to provide description of roles and influences women in government.